Pengaruh Evaluasi Pembelajaran Pendidikan Agama Islam Terhadap Hasil Belajar Siswa Di SMP Muhammadiyah 4 Surakarta - Bagas Ali Mukti; Miftahul Huda Nurrokhim Mulathif; Dario Azhari Syaifuddin; Arneth Fandewa; Nurul Latifatul Inayati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Learning evaluation is an important part of the education process. In the context of Islamic Religious Education (PAI), evaluation is not only centered on the knowledge aspect, but also assesses the development of students' religious character. This study aims to examine the influence of learning evaluation on student learning outcomes at SMP Muhammadiyah 4 Surakarta, and to describe the learning strategies applied by educators in an effort to improve these results. This study uses a descriptive qualitative approach with data collection through interviews, observations, and documentation. The results of the study revealed that learning evaluation was carried out in various forms, such as daily assignments, mid-semester tests (PTS), and end-of-semester assessments (PAS). The strategies applied by teachers include providing role models, giving rewards, delivering moral messages, sharing inspiring experiences, and developing honest and polite behavior. Structured and integrated evaluation with this learning strategy has a meaningful impact on student learning outcomes, both in academic aspects and character development.